Conceptual Understanding of Immune System: Implementation of Teams Games Tournament Learning Model Using Kahoot - Rizhal Hendi Ristanto; Nurmasari Sartono; Gempa Fi Syahrurromadhan; Rohayati Rohayati (Universitas Ahmad Dahlan, 2023)
The immune system material requires a level of abstract thinking, this abstract material makes it difficult for students to learn. Complex and abstract subject matter requires a good understanding of concepts. One way to make it easier for students to understand the concept is by actively involving students and planning effective learning through the cooperative learning model of the Teams Games Tournament (TGT) type using Kahoot. The cause of this look at turned into to decide the effect of the Teams Games Tournament (TGT) cooperative learning model using Kahoot on understanding the concept of the immune system. This studies is a quantitative study the use of a quasi-experimental approach with a pretest-posttest non-equal control group design. The instrument grid is based on indicators of understanding the concept according to Anderson & Krathwohl (2001).The average N-Gain inside the experimental class the usage of the TGT Kahoot is higher than N-Gain in the PBL learning model inside the control class, which is 0.85 compared to 0.75. There is an influence of the TGT learning model using Kahoot on students' conceptual understanding of the immune system material. The application this model requires good classroom management and stable internet connection.